Pembentukan Karakter Religius Melalui Pendampingan Pembiasaan Shalat Dhuha di Lingkungan MA NU Al-Faqihiyah Gempol Pasuruan - Miftachul Taubah; Moh Robby Yasir; Muhammad Feri Prasnanda; Muhammad Fuad Zamroni; Puja Lubadasari; Sintia Nor Alfiatul Qomaria; Dini Andriyani (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
The formation of religious character is an integral part of value-based education in Islamic educational institutions. This article discusses the program of habituating Dhuha prayer at MA NU Al-Faqihiyah, Gempol Pasuruan, as an effort to cultivate students' religious character. The community service method employed involves active participation with an educational and habituation approach through congregational Dhuha prayer activities. The program engages teachers as key facilitators in guiding students to understand the essence and practice of Dhuha prayer. The results indicate increased student commitment to performing Dhuha prayer, enhanced spiritual understanding, and the reinforcement of religious values such as discipline, gratitude, and responsibility. This article recommends the implementation of similar models in various educational institutions to support the development of Islamic character.